2022
DOI: 10.1001/jamahealthforum.2022.2663
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in Out-of-Pocket Costs for Naloxone by Drug Brand and Payer in the US, 2010-2018

Abstract: IMPORTANCE Improving access to naloxone is a critical component of the nation's strategy to curb fatal overdoses in the opioid crisis. Standing or protocol orders, prescriptive authority laws, and immunity provisions have been passed by states to expand access, but less attention has been given to potential financial barriers to naloxone access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…To compound this issue, to our knowledge, no studies have evaluated price sensitivity of naloxone for patients. While 1 study identified that naloxone was price inelastic, the study did not specifically examine price elasticity for uninsured individuals and contradicted more recent evidence suggesting that price sensitivity is a barrier to naloxone use, especially for those who are uninsured . In the context of over-the-counter naloxone, lack of appropriate pricing strategies suited to over-the-counter sales may prohibit naloxone use.…”
Section: Discussionmentioning
confidence: 88%
“…To compound this issue, to our knowledge, no studies have evaluated price sensitivity of naloxone for patients. While 1 study identified that naloxone was price inelastic, the study did not specifically examine price elasticity for uninsured individuals and contradicted more recent evidence suggesting that price sensitivity is a barrier to naloxone use, especially for those who are uninsured . In the context of over-the-counter naloxone, lack of appropriate pricing strategies suited to over-the-counter sales may prohibit naloxone use.…”
Section: Discussionmentioning
confidence: 88%
“…Third, only payer policies for Medicaid were examined in this study. Private health plans typically have large variation in naloxone coverage and uninsured individuals are increasingly burdened with out-of-pocket costs ( Peet et al, 2022 ). However, given that all four states are Medicaid-expansion states, a large portion of individuals at risk for opioid overdose are likely covered by Medicaid.…”
Section: Discussionmentioning
confidence: 99%
“…Reimbursement and insurance coverage for naloxone have been increasing among public and private payors ( Sohn et al, 2020 ). However, the price of naloxone without insurance remains high and insurance may only partially cover the expense ( Peet et al, 2022 ). Even though Medicaid beneficiaries face lower costs, these costs may still be a barrier for low-income individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A body of implementation research has also raised questions about the extent to which NALs are capable of increasing naloxone distribution given lack of knowledge among pharmacists about their state NALs (Thakur et al, 2020) and failure to stock naloxone in pharmacies (Abbas et al, 2021;Eldridge et al, 2020;Graves et al, 2019;Meyerson et al, 2018;Spivey et al, 2020). Finally, one criticism of pharmacy-focused laws is that they may not be effective at helping vulnerable or disadvantaged populations who face stigma from prescribers and pharmacists Smart & Grant, 2021) and for whom the often-substantial price of naloxone (Peet et al, 2022) may represent a serious access barrier. However, no study has evaluated differential effects of NALs on naloxone receipt across population subgroups.…”
Section: Introductionmentioning
confidence: 99%